The Influence of company performance on dividend policy investment as a moderating variable - Syafik, Mohammad (Proceeding of International Management Conference and Progressive Papers, 2023)
This research aims to determine the role of investment in influencing the relationship between company performance and dividend policy. Using panel data from manufacturing companies registered in Indonesia. This research uses OLS, fixed effect and random effect moderation regression analysis tests. Next, the Chow test, Lagrange multiplier (LM) test and Hausman test were carried out to determine the best model for drawing conclusions. The results show that company performance has a positive influence on dividend policy. This influence is weakened when the company carries out investment activities which result in lower dividend distributions.